ASSOCIATION BETWEEN PERCEIVED STRESS AND DISORDERED EATING PATTERNS IN UNDERGRADUATE STUDENTS: A CROSS-SECTIONAL STUDY - Danista,; Ali, Nazia (International Journal of Psychosocial Rehabilitation, 2025)
Disordered eating behaviors and elevated stress levels are increasingly prevalent among undergraduate students, potentially affecting both physical and mental health. While stress has been recognized as a contributing factor to maladaptive eating patterns, limited research explores this association within Indian college populations. This study aims to examine the association between perceived stress and disordered eating patterns among undergraduate students and assess the prevalence of eating concerns in relation to body mass index (BMI). A cross-sectional survey was conducted among 80 undergraduate students aged 19–25 years using the Eating Attitudes Test-26 (EAT-26) and the Perceived Stress Scale-10 (PSS-10). Descriptive statistics and multinomial logistic regression were performed using SPSS 26.0 to evaluate the relationship between stress levels, eating attitudes, and BMI. A positive association was found between higher levels of perceived stress and increased disordered eating attitudes. Students with high perceived stress were more likely to report concerns related to body weight, shape, and eating behaviors, and had a greater likelihood of being overweight compared to those with low stress. Moderate stress levels were also associated with elevated concern about eating and body image. The findings indicate a significant association between perceived stress and disordered eating patterns in undergraduate students. These results underscore the need for early screening and integrated mental health support to address stress-related eating behaviors in college populations.